2016
DOI: 10.1016/j.jim.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparative analysis of 2,4-toluene diisocyanate and 1,6-hexamethylene diisocyanate haptenated human serum albumin and hemoglobin

Abstract: Diisocyanates (dNCOs) are low molecular weight chemical sensitizers that react with autologous proteins to produce neoantigens. dNCO-haptenated proteins have been used as immunogens for generation of dNCO-specific antibodies and as antigens to screen for dNCO-specific antibodies in exposed individuals. Detection of dNCO-specific antibodies in exposed individuals for diagnosis of dNCO asthma has been hampered by poor sensitivities of the assay methods in that specific IgE can only be detected in approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Anyhow, respiratory allergens are also haptens that induce harmful health effects by activating the immune system in much the same way as contact allergens, with the main difference being that the symptom upon elicitation is asthma rather than eczema. Albumin and Hb adducts with diisocyanates have been studied both in vitro and in vivo , and it has been shown that the most abundant diisocyanate adducts are Lys-adducts from albumin 56 60 and N-terminal Val adducts of Hb. 60 63 Diisocyanate-adducts of albumin have been shown to be immunogenic 60 , 64 and are believed to be involved in the etiology of sensitization to the diisocyanates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anyhow, respiratory allergens are also haptens that induce harmful health effects by activating the immune system in much the same way as contact allergens, with the main difference being that the symptom upon elicitation is asthma rather than eczema. Albumin and Hb adducts with diisocyanates have been studied both in vitro and in vivo , and it has been shown that the most abundant diisocyanate adducts are Lys-adducts from albumin 56 60 and N-terminal Val adducts of Hb. 60 63 Diisocyanate-adducts of albumin have been shown to be immunogenic 60 , 64 and are believed to be involved in the etiology of sensitization to the diisocyanates.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin and Hb adducts with diisocyanates have been studied both in vitro and in vivo , and it has been shown that the most abundant diisocyanate adducts are Lys-adducts from albumin 56 60 and N-terminal Val adducts of Hb. 60 63 Diisocyanate-adducts of albumin have been shown to be immunogenic 60 , 64 and are believed to be involved in the etiology of sensitization to the diisocyanates. 65 , 66 Further, the levels of MDI-HSA adducts in MDI-exposed individuals have been shown to correlate with symptoms of allergic asthma and with the presence of diisocyanate-specific IgG antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugation between TDI and HSA, cross-linking, and reactivity were demonstrated. 15 Among them, TDI-conjugated HSA at 40:1 was more reactive than the others in enzyme-linked immunosorbent assay (ELISA). Therefore, 40:1 TDI-HSA conjugate was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed with a high ratio (1:1, 5:1, 10:1, and 40:1) of isocyanates (MDI, HDI, TDI) to Alb. 228230 The high concentrations used for the experiment greatly exceeded the levels of human exposure. In industrial workers, the median adduct level of MDI-Alb was 30 fmol/mg Alb (= 0.002 mol MDI-Lys/mol Alb).…”
Section: Albumin Adducts Formed With Toxicants and Carcinogensmentioning
confidence: 99%